Role of intralesional vitamin D3 in cutaneous warts: an interventional study - Kumar, Sweta S.; Awasthi, Sankalp; Kumar, Adesh; Jain, Prateek (International Journal of Research in Dermatology, 2020)
Background: Cutaneous warts are treated primarily with destructive methods such as cryotherapy or electrocautery. These modalities of treatment may be associated with recurrence and scarring in multiple warts. This study aims to evaluate the efficacy and safety of intralesional vitamin D3 in warts. Methods: 88 patients with recalcitrant warts of varying sizes and duration were included in the study. About 0.2 to 0.5 ml vitamin D3 solution (600,000 IU, 15 mg/ml) was injected to the base of the wart. A maximum of 5 warts were injected per session at 3-week intervals until resolution or for a maximum of 4 treatments. Patients were followed up for 6 months after the last injection to detect any recurrence. Results: 88 patients completed the study. Complete response was seen in 63 out of 88 (71.5%), partial response in 24 out of 88 (27.2%), and no response seen in one patient. The average number of injections required to achieve a complete resolution was 3.66. Complete resolution of distant warts was noticed in all the patients. Conclusions: Intralesional vitamin D3 is a safe, effective, and an inexpensive treatment option for recalcitrant warts.